Library activities on the organization of population leisure: the terminological aspect - E. V. Miroshnichenko; E. A. Beletskaya (Библиосфера)
The terminological analysis of the notions used in library theory and practice: «socio-cultural», «cultural and leisure», «leisure» activities is made; feasibility of using the term «leisure activity» as a synthesizing notion is proved.